Pembuatan alat ukur momen inersia benda digital menggunakan sensor optocoupler - Nunung Rivia (PILLAR OF PHYSICS, 2016)
The moment of inertia is the tendency of an object to remain stationary or move straight regular (maintaining position or situation). The moment of inertia of an object can be measured using a measuring instrument works on the moment of inertia oscillation method. The purpose of this study was to design a measuring tool moment of inertia of objects digitally using optocoupler sensor, as well as explaining the specification of performance, accuracy and precision of the system. Three are  results of this study. First, the performance specifications of the system consists of mechanical systems and is supported by an electronic system. Second, the measurement accuracy by comparing the calculation results with the system theoretically has an average error percentage 3,948% and 96,05% for the relative accuracy of the measurement of some moments of inertia of the object. Third, the precision measurements carried out by measuring the variation of the moment of inertia for 6 items and 10 repetitions with precision the average was 0,979 with a standard deviation of the average 0,000009152 and relative error average 0,834%